Validation of the Slovenian version of multiple sclerosis quality of life (MSQOL-54) instrument - Štern, Biljana (Zdravstveno varstvo, 2017)
Purpose. To cross-culturally adapt and validate Multiple Sclerosis Quality of Life-54 (MSQOL-54) instrument. Methods. The study which enrolled 134 Slovenian multiple sclerosis (MS) patients was conducted from March to December 2013. The internal consistency of the MSQOL-54 instrument was evaluated by Cronbach's alpha coefficient (alpha), and its dimensionality assessed by the principal component analysis (PCA). Results. The whole instrument had high internal consistency (alpha=0.88), as well as the majority of its twelve subscales (alpha=0.83-0.94). The results of the PCA showed two components with eigenvalue greater than 1, explaining 59.4% of the cumulative variance. Further results indicated good construct validity of the instrument with the physical health-related-quality-of-life subscales loading highly on the physical component, and mental health-related-quality-of-life subscales loading highly on the mental component. Conclusion. The Slovenian version of the MSQOL-54 instrument proved to be an internally consistent and accurate tool, well accepted by the Slovenian MS patients. The adequate psychometric properties warrant the scientifically sound version of the MSQOL-54 instrument, which is from now on at disposal to all health professionals dealing with MS patients in Slovenia.
Keywords: MSQOL-54 instrument; multipla skleroza; multiple sclerosis; reliability; vprašalnik MSQOL-54; zanesljivost